2018
DOI: 10.1101/446443
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Focusing on what matters: Modulation of the human hippocampus by relational attention

Abstract: Hippocampal episodic memory is fundamentally relational, consisting of links between events and the spatial and temporal contexts in which they occurred. Such relations are also important over much shorter time periods, during online visual perception. For example, how do we assess the relative spatial positions of objects, their temporal order, or the relationship between their features? Here, we investigate the role of the hippocampus in such online relational processing by manipulating visual attention to d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 95 publications
2
6
0
Order By: Relevance
“…The results reported here are in line with these studies in that they highlight the variety of resting-state networks to which the MTL contributes. Specifically, although resting-state studies can only make limited claims about function, our observation of the MTL in visual and dorsal attention networks seem to be in line with previous studies that have emphasized the implication of MTL in perception and attentional processes (Aly and Turk-Browne 2016;Córdova et al 2019;. The current observation that the MTL is involved in four different resting-state networks, therefore, further underscores the notion that the MTL may be involved in a more abstract type of processing (e.g., relational) that plays an important part in many different cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The results reported here are in line with these studies in that they highlight the variety of resting-state networks to which the MTL contributes. Specifically, although resting-state studies can only make limited claims about function, our observation of the MTL in visual and dorsal attention networks seem to be in line with previous studies that have emphasized the implication of MTL in perception and attentional processes (Aly and Turk-Browne 2016;Córdova et al 2019;. The current observation that the MTL is involved in four different resting-state networks, therefore, further underscores the notion that the MTL may be involved in a more abstract type of processing (e.g., relational) that plays an important part in many different cognitive domains.…”
Section: Discussionsupporting
confidence: 90%
“…Although the MTL is traditionally linked with episodic memory (e.g., Squire & Zola-Morgan 1991), more recent studies have shown the involvement of this structure in a wide range of cognitive functions such as short-term memory (Ranganath and Blumenfeld 2005), visual perception (Barense et al 2012), attention (Aly and Turk-Browne 2016;Córdova et al 2019;, and language and conceptual processing (Duff and Brown-Schmidt 2012;Mack et al 2016;Piai et al 2016). For example, a recent study by revealed that patients with MTL lesions showed impaired performance in an attention task that relied on visual perception suggesting that the MTL plays a role in attention processes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, decreased univariate activity in the hippocampus has been observed along with enhanced multivariate pattern similarity signals -multivariate signals that correlate with behavior (Aly & Turk-Browne, 2016a, 2016bCordova, Turk-Browne, & Aly, 2019). In fact, reduced hippocampal activity has been observed in a task that requires intact hippocampal function for accurate performance (Aly & Turk-Browne, 2016b;Ruiz, Meager, Agarwal, & Aly, 2019).…”
Section: Retrieval and Encoding Modes: Competition Or Cooperation?mentioning
confidence: 99%
“…To date, there is a lack of consensus regarding the role of the medial temporal lobes (MTLs), particularly the hippocampus, in memory‐guided attention. The MTLs are thought to be involved in memory‐guided attention because of their involvement in associative learning (Córdova, Turk‐Browne, & Aly, 2019; Goh et al, 2004; Hannula & Ranganath, 2009; Henke, 2010; Hirsh, 1974; Konkel & Cohen, 2009; Olsen, Moses, Riggs, & Ryan, 2012; Schacter, Dobbins, & Schnyer, 2004). In memory‐guided attention tasks, the making of target‐to‐context associations appears to be critical in order to guide attention.…”
Section: Neural Correlates Underlying Memory‐guided Attentionmentioning
confidence: 99%
“…The second stage then involves cortical structures, such as prefrontal areas, to mediate higher‐order control processes. Further, research has examined the bidirectional relationship between the hippocampus and attention (Aly & Turk‐Browne, 2016a, 2016b, 2017; Córdova et al, 2019; Decker & Duncan, 2020; Günseli & Aly, 2020; Hasselmo, Bodelón, & Wyble, 2006) and suggests that the hippocampus mediates external attention and perception, while attention acts on the hippocampus to stabilize its representations. Although these findings do not speak directly to the effect of memory on attention, they highlight the interactive nature of memory and attention and could be incorporated in future work on the interaction between attention at encoding and then memory‐guided attention at retrieval.…”
Section: Neural Correlates Underlying Memory‐guided Attentionmentioning
confidence: 99%